Digital Tax Avoidance in the Era of Core Tax Administration: Exploring Technical Loopholes and the Illusion of Compliance in Indonesia - Hartono Hartono; Yusuf Yusuf (SEAN Institute, 2026)
The digital transformation of tax administration is expected to improve administrative efficiency, transparency, and voluntary taxpayer compliance. Nevertheless, the implementation of Indonesia's Core Tax Administration System (CoreTax) has also introduced technological vulnerabilities that may create new opportunities for tax avoidance. This study aims to identify the technical loopholes emerging during CoreTax implementation and examine how these vulnerabilities influence taxpayer behavior in the digital tax environment. An instrumental qualitative case study approach was employed, using semi-structured interviews with 17 participants comprising tax officials, tax consultants, corporate taxpayers, and taxation academics, complemented by document analysis. The findings reveal four major technical loopholes: data migration gaps, validation delays, algorithmic blind spots, and authentication weaknesses. These vulnerabilities encourage three adaptive tax avoidance strategies, data omission, timing exploitation, and transaction shifting, while simultaneously fostering an illusion of compliance, whereby taxpayers perceive successful system validation as evidence of substantive compliance. Based on these findings, this study proposes the concept of Digital Tax Avoidance, extending Tax Compliance Theory and Information Asymmetry Theory by incorporating technological vulnerabilities into taxpayer behavior. The study concludes that digital tax transformation should be accompanied by continuous system refinement, stronger real-time validation, enhanced authentication mechanisms, and adaptive risk-based monitoring to minimize digital tax avoidance and strengthen the integrity of modern tax administration.